Cooperative Integrated Reading and Composition (CIRC) and Reading Motivation: Examining The Effect on Students’ Reading Ability - Husni Mubarok; Nina Sofiana (Bina Nusantara University, 2017)
This study examined the effect of Cooperative Integrated Reading and Composition (CIRC) and reading motivation on students’ reading ability. The design of the study was the factorial design of experimental research. The research was conducted on one state junior high school in Jepara Municipality under the Ministry of National Education. The independentvariable of this research was teaching strategies which were classified into two; those who used CIRC as the experimental group and those who used conventional teaching strategy as the control group; while reading motivation, as the moderator variable, was classified into high and low motivation. Students’ reading ability was considered as a dependent variable. This research used 68 students as respondents selected through simple random sampling. The research was analyzed by using multifactor analysis of variance (two-way ANOVA). The research reveals that teaching strategies differ significantly from one another in their effect on the students’ reading ability. The students with high motivation perform better in their reading ability than low-motivation students, regardless of the teaching strategy used. Nevertheless, there is no significant interactioneffect of teaching strategy and reading motivation on students’ reading ability. It means that the effect of teaching strategy on the students’ reading ability does not depend on the students’ reading motivation where F-test (3,326) is lower than (<) F-table 3,99. at 0,05 significance level.